Improved cognitive outcomes in patients with relapsing–remitting multiple sclerosis treated with daclizumab beta: Results from the DECIDE study. (May 2018) - Benedict, Ralph HB; Cohan, Stanley; Lynch, Sharon G; Riester, Katherine; Wang, Ping; Castro-Borrero, Wanda; Elkins, Jacob; Sabatella, Guido
Background: Cognitive impairment is common in multiple sclerosis (MS), with cognitive processing speed being the most frequently affected domain. Objective: Examine the effects of daclizumab beta versus intramuscular (IM) interferon (IFN) beta-1a on cognitive processing speed as assessed by Symbol Digit Modalities Test (SDMT). Methods: In DECIDE, patients with relapsing–remitting multiple sclerosis (RRMS) (age: 18–55 years; Expanded Disability Status Scale (EDSS) score 0–5.0) were randomized to daclizumab beta ( n  = 919) or IM IFN beta-1a ( n  = 922) for 96–144 weeks. SDMT was administered at baseline and at 24-week intervals. Results: At week 96, significantly greater mean improvement from baseline in SDMT was observed with daclizumab beta versus IM IFN beta-1a ( p  = 0.0274). Significantly more patients treated with daclizumab beta showed clinically meaningful improvement in SDMT (increase from baseline of ⩾3 points ( p  = 0.0153) or ⩾4 points ( p  = 0.0366)), and significantly fewer patients showed clinically meaningful worsening (decrease from baseline of ⩾3 points ( p  = 0.0103)). Odds representing risk of worsening versus stability or improvement on SDMT were significantly smaller for daclizumab beta ( p  = 0.0088 (3-point threshold); p  = 0.0267 (4-point threshold)). In patients completing 144 weeks of treatment, the effects of daclizumab beta were generally sustained. Conclusion: These results provide evidence for a benefit of daclizumab beta versus IM IFN beta-1a on cognitive processing speed in RRMS. Trial registration: ClinicalTrials.gov identifier NCT01064401 (Efficacy and Safety of BIIB019 (Daclizumab High Yield Process) Versus Interferon β 1a in Participants With Relapsing-Remitting Multiple Sclerosis (DECIDE)):https://clinicaltrials.gov/ct2/show/NCT01064401 .